StarNet introduces PC X server capable of re-displaying full Unix/Linux console (Telecomworldwire, 2009)
The new release also allows Windows users to run 'LIVE Indirect' sessions, in which the Windows-based X server first connects to the company's secure gateway server. From there, the LIVE Indirect connection makes a secure connection to applications hosted on Linux and Unix servers on the LAN.